2015
DOI: 10.1590/1679-78251469
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and comparison of behavior of corrugated steel plate shear walls

Abstract: In this paper, the nonlinear behaviour of steel plate shear walls with corrugated plates under lateral pushover loading conditions in the models' top level has been analytically investigated by the finite element method. The one-storey frames have beams and columns as boundary elements. Steel plate shear walls are simulated using the finite element method, based on the available experimental models in the literature. After calibration of the analytical models, more parameters of steel shear walls with corrugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…SCPSWs commonly have boundary beams and columns using welded or bolted connections [9][10][11]. Over the past decades, numerous investigations have been conducted on the behavior and design of the SCPSWs [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Among them, the elastic buckling, load resistance, and hysteretic behaviors of SCPSWs under in-plane shear loads were comprehensively evaluated, which can provide valuable references for the design of SCPSWs in practice [8].…”
Section: Introductionmentioning
confidence: 99%
“…SCPSWs commonly have boundary beams and columns using welded or bolted connections [9][10][11]. Over the past decades, numerous investigations have been conducted on the behavior and design of the SCPSWs [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Among them, the elastic buckling, load resistance, and hysteretic behaviors of SCPSWs under in-plane shear loads were comprehensively evaluated, which can provide valuable references for the design of SCPSWs in practice [8].…”
Section: Introductionmentioning
confidence: 99%
“…To assess the matching relationship, the in-plane and out-of-plane stiffness ratio is presented. Yadollahi et al [8] studied the nonlinear behaviour of the sinusoidal and trapezoidal corrugated SPSWs under the lateral pushover loading conditions by numerical simulation. The simulation results found that the property of the trapezoidal CSPSWs is better than sinusoidal CSPSWs.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of Steel plate shear walls (SPSW) considerably depends on the infilled steel plate. Several kinds of research have shown that using stiffened and unstiffened steel plates can affect the load capacity, ductility, and energy dissipation capacity of the steel walls [1][2][3][4][5][6][7][8][9][10][11][12]. Using corrugated steel plates, in the shape of trapezoids, as stiffened infilled steel plates has been of interest to researchers [13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%